QT Dispersion Changes after Transcatheter Aortic Valve Implantation in Patients with Aortic Stenosis - Mustafa Zungur (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: The aim of this study was to evaluate the QT dispersion and echocardiographic parameters in patients before and after transcatheter aortic valve implantation (TAVI). Methods: One hundred and fifty-two patients with severe aortic valve stenosis (AS) were included in our study. Ninety five patients who underwent aortic valve replacement with TAVI were included in the TAVI group and 57 patients, who refused TAVI, were included in the medical treatment group. The QT interval and echocardiographic parameters of all patients were assessed before and after the procedure (first and sixth months and first year). The QT intervals were taken from the onset of the QRS to the end of the T wave. Results: All patients had severe AS. The average mean aortic valve gradient was 46.1±12. Left ventricular internal diastolic diameter (LVIDD) and interventricular septum diastolic thickness (IVSDT) did not change signiﬁcantly after TAVI (P>0.05). QT dispersion, corrected QT dispersion, and mean aortic valve gradient changed signiﬁcantly six months after TAVI (P<0.05). Compared to the medical treatment group, QT dispersion and corrected QT dispersion were significantly decreased at the sixth month in the TAVI group. The incidence of malignant arrhythmias was smaller in the TAVI group than in the medical treatment group. The mortality rate was lower at the first-year follow-up in the TAVI group than in the medical treatment group. Conclusion: Increased QT dispersion is associated with severe symptomatic AS. After TAVI, QT dispersion reduces.